2004
DOI: 10.1038/nature02290
|View full text |Cite
|
Sign up to set email alerts
|

Organization of genetic variation in individuals of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal (AM) fungi (Glomeromycota) are thought to be the oldest group of asexual multicellular organisms. They colonize the roots of most land plants, where they facilitate mineral uptake from the soil in exchange for plant-assimilated carbon. Cells of AM fungi contain hundreds of nuclei. Unusual polymorphism of ribosomal DNA observed in individual spores of AM fungi inspired a hypothesis that heterokaryosis--that is, the coexistence of many dissimilar nuclei in cells--occurs throughout the AM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(212 citation statements)
references
References 23 publications
9
192
2
4
Order By: Relevance
“…Differential selection across ploidy levels has been observed in different abiotic environments (e.g., Dhar et al 2011) and increased ploidy has been suggested to provide a selective advantage in adaptation to new environmental conditions (Pawlowska and Taylor 2004;Ma et al 2009). However, despite the strong selection pressure that is expected in serpentine soils and a report of possible influences of serpentine on the evolution of polyploids in K. arvensis (Kolář et al 2012), we did not find significant differentiation in genome size between the C. geophilum populations included in this study, suggesting that genetic and demographic processes are more important in shaping the genome size variation of this species than environmental selection in the form of home soil chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Differential selection across ploidy levels has been observed in different abiotic environments (e.g., Dhar et al 2011) and increased ploidy has been suggested to provide a selective advantage in adaptation to new environmental conditions (Pawlowska and Taylor 2004;Ma et al 2009). However, despite the strong selection pressure that is expected in serpentine soils and a report of possible influences of serpentine on the evolution of polyploids in K. arvensis (Kolář et al 2012), we did not find significant differentiation in genome size between the C. geophilum populations included in this study, suggesting that genetic and demographic processes are more important in shaping the genome size variation of this species than environmental selection in the form of home soil chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…This high genetic variation may be either intersporal (Pringle et al, 2000) or intrasporal (Clapp et al, 1999). Hypothesis of either heterokaryosis (Kuhn et al, 2001) or homokaryosis (Pawlowska and Taylor, 2004) was proposed to explain the origin of the unusual polymorphism of AMF ribosomal DNA. We were unable to address this issue in our study because DNA was extracted from multiple spores of the reference isolates for PCR-DGGE analysis.…”
Section: Amf Ribosomal Dna Polymorphismmentioning
confidence: 99%
“…This has led some to claim that spores contain ribosomal DNA from several different morphospecies (Clapp et al ., 2001). The extent to which such variation reflects simple polymorphism among multiple copies of rDNA in a single genome or multigenomic mycelia is still controversial (Sanders, 2002;Sanders et al ., 2003;Pawlowska & Taylor, 2004). Individual spores can contain a thousand or more nuclei, and it is normal to recover multiple sequences by polymerase chain reaction (PCR) amplifications from a single spore (Lanfranco et al ., 1999;Antoniolli et al ., 2000;Pawlowska & Taylor, 2004).…”
Section: Morphological Vs Molecular Approachesmentioning
confidence: 99%
“…The extent to which such variation reflects simple polymorphism among multiple copies of rDNA in a single genome or multigenomic mycelia is still controversial (Sanders, 2002;Sanders et al ., 2003;Pawlowska & Taylor, 2004). Individual spores can contain a thousand or more nuclei, and it is normal to recover multiple sequences by polymerase chain reaction (PCR) amplifications from a single spore (Lanfranco et al ., 1999;Antoniolli et al ., 2000;Pawlowska & Taylor, 2004). Second, the diversity of sequences detected depends on the details of the molecular screening approach taken, and many (if not all) approaches currently in use are inherently unable to detect all rDNA sequences present (Redecker, 2000;Vandenkoornhuyse et al ., 2002;Redecker et al ., 2003;Schussler et al ., 2003).…”
Section: Morphological Vs Molecular Approachesmentioning
confidence: 99%